2007
DOI: 10.1007/s10792-007-9103-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and central retinal vein occlusion in Iranian population

Abstract: Elevated total plasma homocysteine level is an independent risk factor for CRVO in Iranian population. In addition to an evaluation of all conventional cardiovascular risk factors, measurement of total homocysteine for evidence of hyperhomocysteinemia may be important in the initial investigation and management of patients with CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Homocysteine was found to be elevated in various other population-based studies such as the Iranian and the Chinese. They reported it as a risk factor for CRVO 19 20. Similar to our earlier study, Latanzio et al 21 reported that homocysteine was the risk factor for early onset CRVO.…”
Section: Discussionsupporting
confidence: 79%
“…Homocysteine was found to be elevated in various other population-based studies such as the Iranian and the Chinese. They reported it as a risk factor for CRVO 19 20. Similar to our earlier study, Latanzio et al 21 reported that homocysteine was the risk factor for early onset CRVO.…”
Section: Discussionsupporting
confidence: 79%
“…The estimates from studies in which control patients had mostly other diseases were fairly homogenous. 18,10,22,24,30,45,58,59,60 The mean tHcy was 1.83 mol/L (95% CI, 1.3-2.3; PϽ0.001) greater in cases than in the controls in this group.…”
Section: Total Homocysteinementioning
confidence: 73%
“…By undertaking a matched pair type of case control study, we could address the confounding effect of age and gender that was noted in different studies in the past. [78910] Hyperhomocysteinemia was a significant independent risk factor for RVO. In view of strict exclusion criteria, our study also ruled out other causes of CRVO affecting the association.…”
Section: Discussionmentioning
confidence: 99%